The relationship between agility and vertical jump performance in male handball players: A cross-sectional analysis on the role of developmental characteristics - Rıdvan Ergin; Betül Karcı (PLoS ONE, 2025)
Aim This research examines the relationship between agility and vertical jump by controlling for developmental characteristics (age, height, and body weight), which are important for sports performance yet underexplored in literature. Materials and methods In this quantitative research, the study group was determined by power analysis and participants were selected using purposive sampling method. The study group consists of 15 male handball players (age 24.1 ± 5 years) who volunteered to participate. Agility performance was determined by the “Illinois Test”, while jumping performance was assessed by the “Vertical Jump Test”. The Pearson test was used in the relationship analysis as a result of the normality assumption. Additionally, a partial correlation analysis was conducted to control for the effect of developmental characteristics (α = 0.05). Results A positive significant relationship was found between age and years of sports (r = .759; p < 0.01) and vertical jump (r = .657; p < 0.01) in male handball players, as well as a positive significant relationship between body weight and agility (r = .621; p < 0.05). Additionally, while controlling for age (pr = −.557; p = 0.039) and body weight (pr = −.558; p = 0.038), a negative significant relationship was found between agility and vertical jump. Conclusion and suggestions As a result, based on the studies examined, it has been observed that male handball players have a high level of agility and vertical jump performance. At the same time, it has been noted that a decrease in age increases agility performance, while an increase in age enhances jump height. The statistical relationship between agility and vertical jump has only been determined when developmental characteristics are controlled. Therefore, it is suggested that to better clarify the relationship between variables in sports performance research, studies should be conducted with developmental characteristics controlled. Additionally, trainers should train agility and vertical jump, testing athletes regularly at set intervals throughout the season for performance tracking.